Analisis Pengaruh Pertumbuhan Ekonomi, Upah Minimum Kabupaten, dan Pengangguran, terhadap Kemiskinan Di Kabupaten Madiun - Oktaviana, Deby; Primandhana, Wiwin Priana; Wahed, Mohammad (Syntax Idea, 2021)
The purpose of this research is to find out about the effects of economic growth, distric minimum wages, and unemployment on poverty in Madiun Regency in 2002-2019. This research utilizes secondary data sources which are data collected by researchers through the statistical center of East Java and Madiun. By adopting a quantitatibe approach method through multiple linear regression analysis with the Ordinary Least Square (OLS) model. This study is able to show an increase in the economy along with the distric minimum wage,so that the influence variabel of economic growth and distric minimum wages on poverty in Madiun Regency is considered to have a significant effect and negative. However, unemployment variabel on poverty in Madiun doesn’t have a significant effect.